The influence of menopausal status on sleep quality in different populations – a narrative review - Skibiak, Klaudia; Dębski, Jan; Przybyłowski, Józef; Walędziak, Maciej; Różańska-Walędziak, Anna (Menopause Review/Przegląd Menopauzalny, 2025)
According to the World Health Organization, menopause occurs between 45–55 years old and is correlated with woman’s family constitution, genetic and environmental factors, place of residence and ethnicity. Menopause is defined as no menstrual bleeding for 12 consecutive months without any pathological or pathophysiological or iatrogenic causes. Hormonal changes may lead to various sleep and mental disorders. Poor sleep quality, difficulty falling asleep or waking up during sleep are among the most important sleep disorders associated with insomnia. Without treatment, insomnia results in chronic daily fatigue, impaired concentration and depressive symptoms. The aim of this review was to conduct an analysis of available studies on the influence of menopausal status on the sleep quality. Cochrane and PubMed databases were searched for original articles, published in 2010–2023, which analyzed the correlation between menopausal status in women of different ethnic groups and their sleep quality. The analysis shows a correlation between the menopausal status and sleep quality, with different intensity in different populations. Most studies show that postmenopausal status is associated with insomnia and poor sleep quality. It is suggested that development of individualized healthcare strategies adjusted for cultural, social and psychological factors would be more effective for women from different populations.